ON PARADIGMATIC AND SYNTAGMATIC RELATIONS ("Conference on Universal Science Research 2023", 2023)
In this article, typical and retail relationships are studied in various aspects. Information is also received about the nature of typical relationships and retail trade. It has been proven that typical relationships allow the choice of the necessary unit when using the language, as well as forming forms and words according to measurement. Or a series of elements of the same arrangement for a specific length, side by side, one by one, on a scientific basis